Fumigant effect of essential oils on mortality and fertility of thrips Frankliniella occidentalis Perg - Stepanycheva, Elena; Petrova, Mariya; Chermenskaya, Taisiya; Pavela, Roman (Environmental science and pollution research international, 2019)
The western flower thrips (Frankliniella occidentalis Perg.) is one of the most economically important insect pests of greenhouse plants. Plant protection against this pest is based predominantly on synthetic insecticides; however, this form of protection poses problems in terms of thrip resistance to the active substances, along with health risks associated with insecticide residues on the treated plants. Therefore, new active substances need to be sought. Essential oils could be a new, appropriate, and safe alternative for greenhouse culture protection. As greenhouses are enclosed areas, fumigation application of EOs is possible. This paper presents acute toxicity results for 15 commercial EOs applied by fumigation, as well as the effect of sublethal concentrations on fertility of F. occidentalis females. The most efficient EOs were obtained from Mentha pulegium and Thymus mastichina, with LC50(90) estimated as 3.1(3.8) and 3.6 (4.6) mg L-1 air, respectively. As found for the very first time, sublethal concentrations of EOs could result in a significant reduction in the fertility of surviving T. occidentalis females. Among the tested EOs, the EO from Nepeta cataria provided the highest inhibition of fertility, with EC50(90) estimated as 0.18 (0.36) mg L-1 air. Chemical composition of the most efficient EOs and possible applications of the results in practice are discussed. In conclusion, in light of the newly determined facts, EOs can be recommended as active substances for botanical insecticides to be applied against Thysanopteran pests by fumigation.
Keywords: Sublethal effect; Mentha pulegium; fertilita; Thrips; Fumigation; Thysanoptera; Insecticides; Greenhouse; Fumigant toxicity; vykuřování; Thymus (rostlina); ženské pohlaví; zvířata; Oils, Volatile; Fertility; Essential oils; oleje prchavé; insekticidy; Botanical insecticides; máta polej; Female; Thymus Plant; Animals